(untitled) - K P. A Menon (New Delhi, India, 1998)
The book is a compilation dealing with the science of policy gathered from the sutras or aphorisms ascribed to Kautilya
Keywords: india - economic conditions,india - history,india - life and customs,india - social conditions,law - india